(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Kuchma O. I., Tsys O. O. Application of information and communication technologies for the organization of educational activities of students of technological and pedagogical specialties. This article explains the specific of the use of informative-communication technologies in organization tekhnologo-pedagogical specialities students’ educational activity . The factors of improvement of students’ quality knowledges are considered at the study of technical disciplines with the use of informative-communication technologies, problems of introduction and use of the educational and controlling computer programs in an educational process and possible ways of their decision.